2010
DOI: 10.1021/ma902817g
|View full text |Cite
|
Sign up to set email alerts
|

Calorimetric Characterization of the Heterogeneities Produced by the Radiation-Induced Cross-Linking Polymerization of Aromatic Diacrylates

Abstract: The structural heterogeneities in networks produced by UV-and by electron beam-initiated polymerization of aromatic diacrylates were unambiguously revealed by AFM imaging and studied by means of temperature-modulated differential scanning calorimetry. Two main second-order thermodynamic transitions were observed during the analysis of diacrylate networks exhibiting a fractional degree of conversion ranging from 0.1 to 0.8. The bimodal distribution of transition temperatures observed as fused peaks in the diagr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 27 publications
0
16
0
1
Order By: Relevance
“…Similar results can be found in the literature. Krzeminski et al, for instance, reported a bimodal distribution of the transition temperatures during the radiation‐induced crosslinking of aromatic diacrylates. In the case of poly(caprolactone)/polylactide copolymer networks, Serra and coworkers concluded about microphase separation due to blending.…”
Section: Resultsmentioning
confidence: 99%
“…Similar results can be found in the literature. Krzeminski et al, for instance, reported a bimodal distribution of the transition temperatures during the radiation‐induced crosslinking of aromatic diacrylates. In the case of poly(caprolactone)/polylactide copolymer networks, Serra and coworkers concluded about microphase separation due to blending.…”
Section: Resultsmentioning
confidence: 99%
“…At the same time, in the literature, it had been suggested, that the presence of microgel agglomerates may adversely affect mechanical properties of poly(dimethacrylate)s, primarily the impact resistance [21,[24][25][26][27][28]. In recent years, with advances in characterization techniques, substantial efforts have been made to precisely describe the polymer network spatial heterogeneity, especially the morphology [29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44][45]. All of this has resulted in many studies on structure-property relationships.…”
Section: Degree Of Conversion (%)mentioning
confidence: 99%
“…It is only in recent years that methodologies for quantitatively characterizing the morphology of dimethacrylate polymer networks have been developed. They utilize AFM supported with advanced mathematical tools [33,34,38,148], X-ray powder diffractometry (XRPD) [32,35,45,136] as well as techniques of thermal analysis: dynamic-mechanical analysis (DMA) [1,42,52,[69][70][71][149][150][151][152][153], differential scanning calorimetry (DSC) [39] and thermogravimetry (TG) [154][155][156].…”
Section: The Morphologymentioning
confidence: 99%
See 1 more Smart Citation
“…The values of IFSS were systematically lower in the case of EB curing, and it is assumed that the little difference in the fraction conversion (0.03) and homogeneity of curing in the sample cannot be the only parameter responsible for it. Indeed, Krzeminski et al . characterized the mechanisms influencing the structure of Ebecryl 600® polymer network and showed that, for the same value of the fraction conversion, it did not depend on the initiation mechanism, the curing temperature and the polymerization timescale.…”
Section: Resultsmentioning
confidence: 99%